The effectiveness of training towards the employees performance: case study in Telekom Malaysia Berhad (TM) Headquarters / Muhammad Aidil Ashmeer Zainol - Zainol, Muhammad Aidil Ashmeer (Faculty of Business and Management, 2015)
Employees are a blood stream of any business. The accomplishment or disaster of the organization or the firms depends on its employee performance. Hence, top management should play their role and the top management realized the important of investing in training and development for the sake of improving employee performance. This conceptual research are aimed at studying the effect of training on employees performance and to provide suggestions to how firm can improve its employees performance through effective training programs. In this research, the studies are mainly focusing on the need of the effective training development towards the employee’s performance. The research also provides the overview of training effectiveness and how it can contributes in enhancing the employee performance in the organization.